Correction of Severe Facial Asymmetry in Patients With Unilateral Craniofacial Microsomia Using Computer-Aided Design/Computer-Aided Manufacturing Technology: An Evaluation of Postsurgical Results. Issue 7 (13th October 2021) - Shetye, Pradip R.; Grayson, Barry H.; McCarthy, Joseph G.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: This is a retrospective study to evaluate the postsurgical position of the maxilla and mandible in 5 matured craniofacial patients with unilateral craniofacial microsomia who underwent 2 jaw surgical procedures using computerized surgical planning. The craniofacial surgeon and orthodontist completed the virtual surgical treatment plan with a biomedical engineer's assistance via a web meeting. The treatment plan of each patient included 2 jaw surgery with genioplasty. At the maxillary dental midline, the planned mean advancement was 4 mm; yaw, a rotational correction towards the unaffected side was 4.96 mm; and impaction was 2.74 mm. The mean advancement measured at point B was 10.5 mm, and the rotational correction towards the unaffected side was 6.58 mm. The mean advancement following genioplasty was 8.43 mm, and the mean transverse correction was 6.33 mm towards the midsagittal plane. The intermediate surgical splint, final surgical splint, bone graft templates, and cutting guides were constructed utilizing computer-aided design/computer-aided manufacturing technology. The surgeon executed the treatment plan in the operating room using appropriate computer-generated guides and splints. A postsurgical cone-beam computed tomography scan was obtained and superimposed on the surgical treatment plan using Simplant OMS 10.1 software. The cranial base was used as a reference for superimposition. Three-dimensional color-coded displacement maps were generated to visually and quantitatively assess the surgical outcome. There was a mean error of 0.88 mm (+0.30) for the position of the maxillary anatomical structures from the planned position, and the anterior mandibular anatomical structures were on average 0.96 mm (+0.26) from the planned position.